University of Pennsylvania Radiocarbon Dates III - Ralph, Elizabeth K. (Radiocarbon, 1959)
The radiocarbon laboratory at the University of Pennsylvania is sponsored jointly by the University Museum and the Physics Department. In this laboratory our primary function is to date archaeologic samples from those four regions of the world in which the University Museum studies are concentrated, namely, the Near East, South America, Central America, and the Arctic. Dates for sites in the first two regions are included in this list, and a long series of temple lintels from Tikal, Guatamala is now being processed. Dates for the Arctic were obtained intermittently from 1953 through 1955 (with solid-carbon counting); others, more recently. The materials for many of the Arctic dates, however, were not reliable; that is, they were physically contaminated before processing in the laboratory. We hope that better samples can be found for future Arctic dating. Our Arctic dates which now furnish tentative age ranges for Punuk, Birnirk, Kachemak Bay III, Okvik, Old Bering Sea, Ipiutak, Norton, Dorset, Kachemak Bay I, Choris, Firth River (Early Mountain Phase), Sarqaq, and Denbigh Flint Complex Periods have been submitted to American Antiquity (Rainey and Ralph, in press) along with detailed discussions of possible contaminations.